Long-Term Outcome and Disability of Diabetic Patients Hospitalized for Diabetic Foot Ulcers - Ghanassia, Edouard; Villon, Laetitia; Thuan dit Dieudonné, Jean-François; Boegner, Catherine; Avignon, Antoine; Sultan, Ariane (Diabetes care, 2008)
Long-Term Outcome and Disability of Diabetic Patients Hospitalized for Diabetic Foot Ulcers A 6.5-year follow-up study Edouard Ghanassia , MD 1 2 , Laetitia Villon , MD 1 2 , Jean-François Thuan dit Dieudonné , MD 1 2 , Catherine Boegner , MD 1 , Antoine Avignon , MD 1 2 and Ariane Sultan , MD 1 2 1 Le Centre Hospitalier Universitaire Montpellier, Montpellier, France 2 Université Montpellier 1, Unités de Formation et de Recherche de Médecine, Montpellier, France Corresponding author: Antoine Avignon, a-avignonatchu-montpellier.fr Abstract OBJECTIVE —The long-term outcome and functional status of subjects hospitalized for diabetic foot ulcers have been poorly studied and thus are the topics of this study. RESEARCH DESIGN AND METHODS —Ninety-four consecutive diabetic subjects hospitalized for diabetic foot ulcers between January 1998 and December 2000 were prospectively followed for mean ± SD 79.5 ± 13.3 months. We calculated rates of primary healing, new ulcers, amputations, mortality, and disability and evaluated the global therapeutic success (GTS) of foot care management as defined by the association of primary healing without recurrence or disability at the end of follow-up. RESULTS —Follow-up was successful in 89 of 94 subjects (63 men and 31 women; age 63.7 ± 10.8 years). Of these, 69 (77.5%) experienced primary healing without major amputation, 39 (43.8%) underwent amputation (24 minor and 15 major), and 46 died (51.7%), including 23 from cardiovascular events. Forty-two of 69 patients who experienced primary healing (60.9%) had ulcer recurrence. At the end of the follow-up period, 25 patients (28.1%) were dependent and 40 subjects (44.9%) had achieved GTS. Multivariate analysis showed the role of age as an independent predictor of GTS ( P < 0.05) and of impaired renal function/albuminuria as independent predictors of healing failure, first amputation, and mortality ( P < 0.01). CONCLUSIONS —Despite a satisfactory initial healing rate, the global long-term outcome of patients hospitalized for diabetic foot ulcers was poor. Nephropathy appears to be an important predictor of long-term outcome. Further studies are needed to establish recognized criteria for therapeutic success going beyond just the evaluation of healing rate in the management of diabetic foot ulcers. Footnotes Published ahead of print at http://care.diabetesjournals.org on 4 April 2008. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted April 1, 2008. Received November 7, 2007. DIABETES CARE